Constitutive expression of an endogenous sugar transporter gene SWEET11 in Indian mustard (Brassica juncea) and its effect thereof on mustard aphids - Zauva, Lianthan; Dhatwalia, Deepa; Subramanian, S; Chamola, Rohit; Bhattacharya, Ramcharan (The Indian Journal of Agricultural Sciences, 2020)
One of the major oil yielding crops Indian mustard [Brassica juncea (L.) Czern. & Coss.] is highly susceptible to mustard aphid, a hemipteran sap sucking insect-pest. Leaf-transcriptome of mustard treated with different aphid species as host and non-host revealed variable expression of three sugar transporter genes. One of these transporters BjSWEET11 was constitutively expressed under a CaMV 35S promoter in B. juncea through Agrobacterium-mediated plant transformation. The transgenic plants after requisite molecular analysis for the presence and expression of the introduced gene were assayed for their deterring effects on the infestation by mustard aphid (Lipaphis erysimi). Attenuating effect of the enhanced BjSWEET11 expression on multiplication and population growth of mustard aphids demonstrated likely involvement of this transporter in endogenous plant defense mechanism.